Euthanasia problem in context of biothetics - Tomas, Theophilie Emilie; Kochubiei, Oksana; Кочубей, Оксана Анатольевна; Кочубєй, Оксана Анатоліївна (KhNMU, 2015)
Is the intentional and painless way of ending the life of the another person, this is done either by act ,by omission or by compassionate motives. Euthanasia is from a Greek word witch is means good death. The question if euthanasia is in fact a good death, is still highly controversial. Euthanasia can be performed in different way, eg: by administering a legal drug, by withdrawing basic heath care which sustain life (such as food, water, or antibiotics). Most of the euthanasia cases happening in medicine is done throughout life support machines, example, during receiving artificial oxygen. Do due to different reasons, such as, economic reasons, as it maybe noticed that keeping the patient can be a financial burden and there is no hope for him to recover. With the rising health care cost, and an aging population in the world , if euthanasia or assisted suicide legalized, this can rise fear that , voluntary euthanasia will be given away to involuntary and used as a way of getting rid of people living with sever disability . History shown that, once society provides approved guideline within which is acceptable to kill another person it is only a matter of time for those quideline to be changed and the range of victims extended. Doctors and healthcare are already making decisions to end the lives of patients deem to have a low quality of life. Opponents of euthanasia feel that, euthanasia enhances the power of Doctors, not patients. Healthy workers and bioethicists argue in favor of futile care theory which measures the value of human life according to the financial cost of keeping the individual alive. Bioethicists believe that people such as people in coma with no hope of wake up, Parkinson patients, patients of mental illnesses are all likely to be at some risks if euthanasia is became legalize. As we are all human, we have to respect the value of another person regardless of what conditions, and I remain strongly believe that, euthanasia must not be legalized, and no doctor must end the life of a patient intentional, unless if the patient himself who is in severe pain with no hope, decided without pressure from family members or from health workers.